Effective Curriculum Management : Co-ordinating Learning in the Primary School. - Kitson, Neil (RoutledgeFalmer, 1996)
The role of the curriculum co-ordinator is a very varied and sometimes frustrating one for already over-worked teachers. Written by experienced teachers, this book is packed with practical advice to help all co-ordinators in their work.